Tooth brushing with fluoridated toothpaste and associated factors among Chinese adolescents: a nationwide cross-sectional study - Zhiying Cui; Wenhui Wang; Yan Si; Xing Wang; Xiping Feng; Baojun Tai; Deyu Hu; Huancai Lin; Bo Wang; Chunxiao Wang; Shuguo Zheng; Xuenan Liu; et al. (BMC, 2023)
Abstract Background Tooth brushing with fluoridated toothpaste has become the most important way to provide the anti-caries effect of fluoride around the world. China has promoted the use of fluoridated toothpaste since 1989. However, there are few studies on the national profile of use of fluoridated toothpaste and related factors in Chinese adolescents. We carried out this study to investigate oral hygiene behaviours, especially the status of tooth brushing with fluoridated toothpaste and its correlates among adolescents, based on data from the latest Nation Oral Health Survey in mainland China. Methods This cross-sectional study recruited 118,601 participants aged 12-15 years using multistage stratified sampling. Questionnaires were completed by students at school. Data employed in analyses were extracted from the questionnaire, including information on tooth brushing, fluoridated toothpaste, dental floss, sociodemographic factors, fluoride knowledge and attitude towards regular dental check-ups. A binary logistic regression was performed to compute the odds ratios (OR). Tooth brushing twice daily with fluoridated toothpaste was the dependent variable. Sociodemographic factors, fluoride knowledge, attitude towards regular dental check-ups, dental visit experience and perceived oral health were the independent variables. P < 0.05 was considered statistically significant. Results A total of 32.6% of participants brushed their teeth twice daily, 7.4% used fluoridated toothpaste, and 3.9% cleaned their teeth twice daily with fluoridated toothpaste. The logistic regression showed the probability of twice-a-day tooth brushing with fluoridated toothpaste was higher among these groups: females (OR: 1.141; 95%CI: 1.072-1.214), 15-year-olds (OR: 1.786; 95%CI: 1.634-1.952), from urban areas (OR: 1.389; 95%CI: 1.288-1.497), without siblings (OR: 1.351; 95%CI: 1.259-1.450), with an educated father (OR: 1. 605; 95%CI: 1.442-1.788) and mother (OR: 1.706; 95%CI: 1.530-1.903), having dental visit experiences (OR: 1.702; 95%CI: 1.589-1.823), rating one's oral health as good (OR: 2.341; 95%CI: 2.083-2.631), having fluoride knowledge (OR: 4.345; 95%CI: 4.034-4.678) and having a positive attitude towards regular dental check-ups (OR: 1.589; 95%CI: 1.460-1.729). Conclusions The oral hygiene behaviours of Chinese adolescents were undesirable. Twice daily tooth brushing with fluoridated toothpaste was significantly associated with sociodemographic factors, fluoride knowledge, and attitudes towards regular dental check-ups.